Incidence Rate of Fascioliosis during Idul Adha 1440 H in Malang City - Paramanandi, Dini Agusti; Wisesa, I Bagus Gde Rama; Kusumarini, Shelly (Veterinary Biomedical and Clinical Journal, 2020)
As an annual Muslim celebration, Eid al-Adha Feast is celebrated every year in Malang City. In 2019 feast, animals were sacrificed in Malang City consisting of 1202 cattle, 3572 goats and 302 sheep. Antemortem and postmortem examination were very important steps to ensure the quality of consumable animal product produced during the feast. The importance of these examination was to prevent zoonotic food-borne and transmissible disease from contaminated animal product to other livestocks nearby. Fascioliosis was listed into routine disease check due to its potential to reduce the quality of animal product, especially the liver. This study was held in 5 sub-districts in Malang City according to descriptive data collected by interview and structural questionnaire as well as visual observation. The result showed that fascioliosis happened in 26,03% of cattle, 2,93% of goats, and 1,32% of sheep being slaughtered. We also analized several risk factors influencing fascioliosis incidence rate such as body score condition and age. The fascioliosis tent to happen in medium and mature animal by age in respectively 31,62% of cattle, 54,28% of goats, and 75% of sheep. Thus, prevention and curative evaluation of fascioliosis should be continuously developed in order to provide excellent animal products.